Efficacy Using a Modified Technique for Tissue Stabilized-Guided Subcision for the Treatment of Mild-to-Moderate Cellulite of the Buttocks and Thighs. Issue 10 (October 2018) - Ibrahim, Omer; Haimovic, Adele; Lee, Nicole; Kaminer, Michael S.
Abstract : BACKGROUND: Cellulite can be significantly improved using vacuum-assisted tissue stabilized-guided subcision (TS-GS). However, the treatment of shallow and linear cellulite has remained problematic. OBJECTIVE: In this retrospective study, we describe a modified technique of vacuum-assisted TS-GS. The aim is to demonstrate that this new limited-release technique is an effective treatment for long ripples and interconnected shallow dimples, which are characteristic of mild-to-moderate cellulite. METHODS: Patients with mild-to-moderate cellulite were treated with limited-release vacuum-assisted TS-GS. All subcisions were performed at the 6-mm depth and a minimum of 3 mm between each dimple. Using a 4-point scale, 2 raters graded cellulite improvement on evaluation of prephotographs and postphotographs. RESULTS: A total of 23 female patients were included in this study. The pre- and post-treatment photographs were correctly identified in 22 of the 23 patients (95.6%). The average cellulite improvement was 2.9 of 4 for the buttocks and 2.8 of 4 for the posterior thighs. Global cellulite improvement was reported at 3.1 of 4. CONCLUSION: The results demonstrate that modified, limited-release, vacuum-assisted TS-GS can be an effective and safe method for the treatment of long ripples and shallow dimples that are characteristics of mild-to-moderate cellulite.